2006
DOI: 10.4049/jimmunol.177.7.4670
|View full text |Cite
|
Sign up to set email alerts
|

Murine γ-Herpesvirus 68 Limits Naturally Occurring CD4+CD25+ T Regulatory Cell Activity following Infection

Abstract: During microbial infections, naturally occurring CD4+CD25+ T regulatory cells can suppress protective host responses or they can limit pathogen-induced inflammatory responses. The particular role played by these cells seems to depend upon the infectious agent being investigated. γ-Herpesviruses are efficacious pathogens which are well-known for their ability to induce lymphoproliferative disease and to establish latency in the host. However, no studies have investigated the importance of naturally occurring CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…Murine gamma-herpesvirus 68 infection reduces Treg numbers and inhibits their function, although the underlying mechanisms are undefined (40). The human T cell lymphotropic virus type I-associated virus-encoded tax protein inhibits Foxp3 expression and suppressor function (41).…”
Section: Discussionmentioning
confidence: 99%
“…Murine gamma-herpesvirus 68 infection reduces Treg numbers and inhibits their function, although the underlying mechanisms are undefined (40). The human T cell lymphotropic virus type I-associated virus-encoded tax protein inhibits Foxp3 expression and suppressor function (41).…”
Section: Discussionmentioning
confidence: 99%
“…Ag-specific regulatory T cells have long been implicated in dampening down inflammatory responses by reducing CD4 ϩ T cell activation; recent publications have demonstrated that MHV-68 can limit CD4 ϩ CD25 ϩ activity and decrease Foxp3 expression in splenic CD4 ϩ T cells (21). We therefore analyzed changes in the Foxp3 expression of transferred CFSE-labeled BDC2.5NOD CD4 ϩ T cells and of endogenous CD4 ϩ T cells and quantified the numbers of CD4 ϩ regulatory T cells within the PLN of MHV-68 infected and uninfected NOD mice.…”
Section: Changes In Autoreactive T Cell Activation Are Not Associatedmentioning
confidence: 99%
“…Virus stock was prepared by infecting BHK-21 cells [American Type Culture Collection (ATCC), Rockville, MD; CCL-10) with HV-68 at a low multiplicity of infection, followed by isolation of virus as previously described [31][32][33][34][35][36]. Replicating virus present in viral stocks was quantified using serial dilutions on NIH-3T3 cell (ATCC CRL 1658) monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal inoculations with HV-68 were performed as previously described [31][32][33][34][35][36]. Briefly, mice were anesthetized and allowed to aspirate, via the nasal passages, 20 ml of inoculum containing 6,000 plaque-forming units of HV-68.…”
Section: Intranasal Inoculation With Hv-68mentioning
confidence: 99%
See 1 more Smart Citation